Synthesis, Spectral Characterization, Docking Studies and QSAR Screening of 4-amino-benzenesulfonamides/N-acetyl 4-amino-benzenesulfonamide Derivatives as Antimicrobial Agents - Ajeet; Laxmi Tripathi; Arvind Kumar (Journal of Pharmacy and Nutrition Sciences, 2014)
A series of substituted 4-amino-benzenesulfonamides / N-acetyl-4-amino-benzenesulfonamide were designed & synthesized keeping in view the structural requirements of pharmacophore and were evaluated for in-silicoantimicrobial activity. For establishing the structure, spectral characterization like FT-IR, 1H NMR, GC-MS and elemental analysis (CHNS) has been performed. The antimicrobial activity of the titled compounds was assessed using in-silico studies (QSAR screening and Docking). It was carried out for the prediction of pharmacokinetic properties and to study the binding properties of drugs with molecular targets. Titled compounds exhibited good binding properties with molecular target. It could be concluded that molecular target responsible for the antimicrobial activity of substituted 4-amino-benzenesulfonamides / N-acetyl-4-amino-benzenesulfonamides may be pseudomonas aeruginosa exotoxin A.